Missing White woman - Garrett, Kellye, 1978- (Mulholland Books / Little, Brown and Company, 2024)
For their romantic getaway to New York City, Breanna's new boyfriend, Ty, took care of everything--the train tickets, the dinner reservations, the luxury row house where they stayed. But on the final morning, when Breanna came downstairs, she found a dead white woman in the foyer, and Ty was gone. The woman is Janelle Beckett, a missing person with a social media following, #Justice4Janelle. Breanna's only hope for staying out of jail is her ex-best friend, a lawyer with whom she shares a complicated past. Bree realizes that the only way she can help Ty--or herself--is to figure out what really happened that last night. But when people only see what they want to see, can she uncover the truth hiding in plain sight?" --